1997
DOI: 10.1136/adc.76.4.304
|View full text |Cite
|
Sign up to set email alerts
|

Relation between insulin-like growth factor-I, body mass index, and clinical status in cystic fibrosis

Abstract: Objectives-Despite improved nutrition and intensive treatment, subjects with cystic fibrosis have diYculty in maintaining anabolism during intercurrent infections, which can result in reduced body mass index and impaired skeletal growth. Insulin-like growth factor-I (IGF-I) and its binding protein IGFBP3 are sensitive to changes in nutritional status. The aim of this study was to determine the relation between circulating concentrations of these peptides, body mass index, and clinical status in cystic fibrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
5
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 44 publications
8
46
5
6
Order By: Relevance
“…Serum IGF-I levels were significantly lower in CF patients than in controls. At variance with previous studies this did not seem to be dependent on malnutrition or anorexia (9,14,28,29) as the BMI values of these patients were normal and similar to those of controls, and total serum protein concentration was normal. Other authors have hypothesized that low serum IGF-I concentrations could be dependent on insulin hyposecretion in CF.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Serum IGF-I levels were significantly lower in CF patients than in controls. At variance with previous studies this did not seem to be dependent on malnutrition or anorexia (9,14,28,29) as the BMI values of these patients were normal and similar to those of controls, and total serum protein concentration was normal. Other authors have hypothesized that low serum IGF-I concentrations could be dependent on insulin hyposecretion in CF.…”
Section: Discussioncontrasting
confidence: 85%
“…IGFBP-3 serum concentrations were similar in the patients and controls although they tended to be lower in patients with the most severe clinical state, and we did not find any relationship with insulin at variance with previously published data (28,29). This helps to explain why the IGF-I/IGFBP-3 molar ratios were similar in CF and healthy subjects.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…To determine whether rhIGFBP-3 treatment affected systemic levels of Igf-I or Igfbp-3, the serum levels of these proteins were measured. As shown in Figure 5A, Igf-I was lower in serum from CF versus non-CF mice (p ϭ 0.003) as has been reported for CF patients (17) and CF mice (18), whereas Igfbp-3 levels were significantly increased (p ϭ 0.002). Serum levels of Igfbp-3 have not been reported for CF mice, whereas in CF patients, these measures have been shown to be lower (17) or unaltered (19); neither measure was significantly altered by rhIGFBP-3 treatment.…”
Section: Expression Of Igf Pathway Genes Is Altered In Intestines Of supporting
confidence: 76%
“…Several studies have shown significant deficits of Igf-1 in CF patients (27)(28)(29). The behavior of GH in CF patients is more equivocal, with studies showing higher, normal, or lower levels of the hormone [reviewed in (28)].…”
Section: Growth In Cystic Fibrosis Micementioning
confidence: 99%